Adolescent Assent and Reconsent for Biobanking: Recent Developments and Emerging Ethical Issues - Kasperbauer, T. J.; Halverson, Colin (Frontiers in Medicine, 2021)
Research biobanks that enroll minors face important practical, ethical, and regulatory challenges in reconsenting participants when they reach the age of 18. Federal regulations governing research in the United States provide minimal guidance and allow for a range of practices, including waiving the requirement to obtain reconsent. Some commentators have argued that institutional review boards should indeed grant such waivers, given the low risks of biobank-based research and the impracticality of contacting all participants when they turn 18. There is also significant ethical debate about the age at which adolescents can make authentic, autonomous decisions regarding their research participation. This paper reviews these issues in detail, describes the current state of the ethical discussion, and outlines evidence-based policies for enrolling minors into research biobanks.